Energy demand transitions and climate mitigation in low-income urban households in India - Khosla, R; Sircar, N; Bhardwaj, A (IOP Publishing, 2019)
Growing household energy demand, particularly in developing countries starting from a low base of consumption, is an important driver of current and future greenhouse gas emissions. Yet, our understanding of transitioning residential energy demand in developing country contexts is limited. This paper discusses changing energy service demands in urban low-income households in India, an emerging economy where the largest future growth in energy demand globally is projected to occur, and where 12 million new low-income homes for the urban poor are to be built by the government between 2015 and 2022. Based on mixed quantitative and qualitative methods comprising of surveys, interviews and focus group discussions, we analyze two inter-related questions: how does the demand for energy services change as the ability of low-income households to consume increases; and how do energy related behaviors influence household electricity consumption? We analyze the data collected to rank households according to their ability to consume and to identify the types of, and progression in, energy services acquired. The appliances and associated services pursued are lights, fans, televisions, and refrigerators, with varied energy efficiencies. Analogously, we quantify the influence of behavior in determining electricity consumption, and show that the inclusion of socio-demographic and behavioral factors explain a significant proportion (51%) of the variance in household electricity consumption, along with the role of material factors such as building physical characteristics and appliance stocks. We complement the statistical analysis with qualitative fieldwork and discuss changing energy related behaviors as the ability of households to consume increases. We conclude with recommendations for climate actions that are compatible with development in the growing low-income housing stock.